A pilot study on dietary choices at universities : vending machines, canteens, and lunch from home - Oliveira, Leandro (2024)
Commercial environments and food acquisition methods significantly shape dietary practices and impact health. This study assesses dietary choices among Portuguese university students regarding vending machines, canteens, and lunches from home. It also evaluates their use of the university canteen and their tendency to bring lunch from home. This pilot cross-sectional study used a self-administered electronic questionnaire, made available in early 2023. Participants were recruited through snowball sampling. The study included 137 students from Portuguese higher education institutions, mainly women (74.5%), pursuing degrees or integrated Master’s degrees (83.2%), primarily in health-related fields (55.5%). The median age was 21 years (20 to 23.5 years). About 70.0% regularly consumed food from vending machines, while approximately 60.0% brought lunch from home, avoiding the canteen. Factors such as convenience (48.5%), price (47.5%), product availability (40.6%), and taste (39.6%) mainly influenced vending machine choices. Monthly, chocolates, water, coffee, cookies, treats, and soft drinks were the most commonly acquired items, with coffee being the most frequent daily purchase. These findings provide insights for creating policies and initiatives to promote healthier and more accessible food options for students and strategies to encourage positive eating behaviors.